A Parametric Study of Effect On Single Pile Integrity Due to An Adjacent Excavation Induced Stress Release in Soft Clay - Mangnejo, D. A.; Soomro, M. A.; Mangi, N.; Halepoto, I. A.; Dahri, I. A. (Engineering, Technology & Applied Science Research, 2018)
To gain new insights into single pile responses to adjacent excavations in soft ground, numerical parametric studies are carried out. An advanced hypoplastic (clay) constitutive model which takes account of small-strain stiffness is adopted. The effects of excavation depths (i.e. formation level) relative to pile were investigated by simulating the excavation near the pile shaft (i.e., He/Lp=0.67), next to (He/Lp=1.00) and below the pile toe (He/Lp=1.33). Among the three cases, the excavation in case of He/Lp=1.33 resulted in the largest pile settlement (i.e. 7.6%dp). On the other hand, the largest pile bending moment was induced in case of He/Lp=0.67.